effects of free-air CO2 enrichment (FACE) on carbon and nitrogen accumulation in grains of rice (Oryza sativa L.) - Zhang, Guoyou; Sakai, Hidemitsu; Tokida, Takeshi; Usui, Yasuhiro; Zhu, Chunwu; Nakamura, Hirofumi; Yoshimoto, Mayumi; Fukuoka, Minehiko; Kobayashi, Kazuhiko; Hasegawa, Toshihiro (Journal of experimental botany, 2013)
Rising atmospheric CO2 concentrations will probably increase rice (Oryza sativa L.) yield but decrease grain nitrogen (GN) concentration. Grains attached to different positions in the panicles differ greatly in weight and quality, but their responses to elevated CO2 (e[CO2]) are poorly understood, which limits our understanding of the mechanisms of yield enhancement and quality degradation. Thus a free-air CO2 enrichment experiment was conducted to examine the effects of e[CO2] on grain mass (GM), grain carbon (GC), and GN accumulation in the spikelets attached to the upper primary rachis branch (superior spikelets; SS) and those attached to the lower secondary rachis (inferior spikelets; IS). e[CO2] stimulated the rice yield by 13% but decreased the N concentration in the panicle by 7% when averaged over two levels of N fertilizations (P < 0.01). The responses of SS and IS to e[CO2] were different particularly under higher N supply. For SS, e[CO2] decreased GN by 24% (P < 0.01) but did not affect GM. For IS, e[CO2] increased GM by 13% (P < 0.05) but GN was not affected. The reduction of GN due to e[CO2] started to appear at the beginning of grain filling. These results suggest that future [CO2] levels probably stimulate the grain growth of IS, most of which are not marketable due to limited size, at the expense of GN reduction in SS. Translocation of N from SS to IS may be a possible mechanism for reduction in GN of SS. This may degrade the grain quality of marketable rice under e[CO2].